Polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer and preparation method thereof
By preparing polyester-carbon dioxide-based polycarbonate-polyester triblock copolymer, the problem of difficult degradation of existing transparent elastomer materials is solved, and the high strength, ductility and elastic recovery performance of the material is achieved, and the good environmental protection and biodegradability are also achieved.
Patent Information
- Application Number
- CN202510338017.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-21
AI Technical Summary
Existing transparent elastomer materials are difficult to degrade, resulting in environmental pollution and lack of biodegradable materials that have both good thermal and mechanical properties.
By reacting alkoxides of different chain lengths with carbon dioxide, combining tetrachlorophenyl anhydride and epoxide, a polyester-carbon dioxide-based polycarbonate-polyester triblock copolymer with a hard-soft-hard structure was prepared.
It realizes the high strength, high ductility and extremely high elastic recovery performance of the material, and has two glass transition temperatures at the same time, and the material is non-toxic, biodegradable, and has strong environmental protection.
Smart Images

Figure CN119875089A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer and a preparation method thereof. Background Art
[0002] Traditional transparent elastomers mainly include polyurethane elastomers, polyvinyl chloride elastomers and silicone rubber elastomers, etc. These traditional elastomer materials are difficult to degrade, and they enter the environment after being discarded, causing serious "white pollution". Therefore, it is very necessary to develop biodegradable transparent elastomer materials that also have good thermal and mechanical properties.
[0003] The copolymer of alkylene oxide and carbon dioxide (CO2) is a transparent, fully degradable and environmentally friendly plastic. Chinese patent CN109485842A discloses a bio-based elastomer prepared from a copolymer of allyl glycidyl ether and carbon dioxide with a flexible chain, and its glass transition temperature can reach -38.8°C. The terminal double bonds on the side chains can undergo a thiol-ene click reaction with alkyl mercaptan to generate hyperbranched side chains. Chinese patent CN116836390A discloses a method for synthesizing a flexible polythioether rubber, which uses 3,6-dioxy-1,8-octanedithiol, allyl glycidyl ether and trithiol substances to react epoxy with thiol, double bonds with thiol to obtain a dithiol reaction liquid with side hydroxyl groups, and the dithiol reaction liquid is then subjected to an addition polymerization reaction with 1,5-hexadiene to obtain a flexible polythioether rubber, and the synthesized flexible polythioether rubber has a glass transition temperature of below -65°C.
[0004] ABA triblock or multiblock copolymers with microphase separation structure have the thermoplastic processability of plastics and the high elasticity of rubber. In recent years, researchers have begun to focus on the design and synthesis of CO2-based TPE, which is mainly composed of ABA triblock and multiblock structures. This type of triblock copolymer is characterized by a low Tg soft segment in the middle and rigid or strongly interactive hard segments at both ends. Chinese patent CN118206729A discloses a tetrachlorophthalic anhydride / epoxide / carbon dioxide ternary block copolymer and its preparation method. The glass transition temperature of the copolymer prepared by this method can reach 100°C. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer having two glass transition temperatures, one low and one high, high strength, high ductility and extremely high elastic recovery performance and a preparation method thereof. The present invention firstly uses alkoxides of different chain lengths to react with CO2, and uses a cheap, easy-to-obtain, simple and efficient metal catalyst system or a non-metallic Lewis acid and a single-initiator or double-initiator organic ammonium salt two-component catalyst system to catalyze and prepare a relatively soft polycarbonate containing long branches; secondly, tetrachlorophthalic anhydride and epoxide are introduced into the long-chain alkoxide and CO2 copolymerization system, and epoxide and tetrachlorophthalic anhydride are copolymerized to generate relatively hard polyester segments at both ends of the polycarbonate, thereby preparing a triblock polyester-polycarbonate copolymer with a hard-soft-hard structure.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer, which is a tetrachlorophthalic anhydride / epoxide 1 / epoxide 2 / carbon dioxide quaternary triblock copolymer; The epoxide 2 is epoxyhexane, epoxyoctane, butyl glycidyl ether, octyl glycidyl ether or allyl glycidyl ether; When epoxide 2 is oxirane, octane oxide, butyl glycidyl ether or octyl glycidyl ether, tetrachlorophthalic anhydride and epoxide 1 are polymerized to form a hard polyester segment, and epoxide 2 reacts with carbon dioxide to form a soft polycarbonate segment, the structure of which is shown in the following formula (a); If the epoxide 2 is allyl glycidyl ether, a polycarbonate with a double bond at the end of the branch chain is generated. Under ultraviolet light conditions, the terminal double bond further undergoes a thiol-ene click reaction with thiol to obtain a grafted alkyl long chain, the structure of which is shown in the following formula (b):
[0007] Where a≥1, b≥1, and a and b are both integers.
[0008] Preferably, the epoxide 1 is ethylene oxide, propylene oxide, epichlorohydrin or butylene oxide.
[0009] Preferably, when the epoxide 2 is allyl glycidyl ether, the tetrachlorophthalic anhydride / epoxide 1 / allyl glycidyl ether / carbon dioxide tetrablock copolymer further undergoes a thiol-alkenyl click reaction with n-butyl mercaptan, sec-butyl mercaptan, isobutyl mercaptan, n-pentyl mercaptan, 2-pentyl mercaptan, isopentanyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan, n-octyl mercaptan, sec-octyl mercaptan, isooctyl mercaptan, n-decyl mercaptan, n-nonyl mercaptan, tert-nonyl mercaptan, dodecanethiol, tetradecanethiol, hexadecanethiol or n-octadecyl mercaptan to obtain a grafted alkyl long chain.
[0010] A method for preparing a polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer, and a method for preparing a tetrachlorophthalic anhydride / epoxide 1 / epoxide 2 / carbon dioxide quaternary triblock copolymer comprising the following two methods: Method 1: (a) Add part of epoxide 1, epoxide 2, part of tetrachlorophthalic anhydride and a single initiator catalyst into a high-pressure reactor under anhydrous and oxygen-free conditions, introduce carbon dioxide, and react for a period of time under magnetic stirring and heating conditions before stopping; (b) After the reaction is completed, cool the reactor; continue to add the remaining same amount of epoxide 1 and tetrachlorophthalic anhydride under anhydrous and oxygen-free conditions, continue to react for a period of time, and then obtain a purified tetrablock copolymer by precipitation and drying; the molar ratio of total epoxide 1 to epoxide 2 is 1:10~1:1; the molar ratio of epoxide 2 to total tetrachlorophthalic anhydride is 6:1~2:1; the molar ratio of epoxide 2 to single initiator catalyst is 2000:1~500:1; Method 2: (a) Add epoxide 2 and a dual initiator catalyst into a high-pressure reactor under anhydrous and oxygen-free conditions, introduce carbon dioxide, react for a period of time under magnetic stirring and heating conditions, and then stop; (b) After the reaction is completed, cool the reactor; add epoxide 1 and tetrachlorophthalic anhydride under anhydrous and oxygen-free conditions, continue to react for a period of time, and then obtain a purified tetrablock copolymer by precipitation and drying; the molar ratio of epoxide 1 to epoxide 2 is 1:10~1:1; the molar ratio of epoxide 2 to tetrachlorophthalic anhydride is 6:1~2:1; the molar ratio of epoxide 2 to the dual initiator catalyst is 3000:1~1000:1.
[0011] A method for preparing a polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer, wherein the polyester-carbon dioxide-based polycarbonate-polyester triblock copolymer is prepared by reacting tetrachlorophthalic anhydride / epoxide 1 / allyl glycidyl ether / carbon dioxide / thiol, and the method comprises the following steps: (1) Adding a dual initiator catalyst and allyl glycidyl ether into a high-pressure reactor under anhydrous and oxygen-free conditions, injecting carbon dioxide, and reacting for a period of time under magnetic stirring and heating conditions and then stopping; (2) After the reaction is completed, the reactor is cooled to room temperature, and tetrachlorophthalic anhydride and epoxide 1 are added under anhydrous and oxygen-free conditions. The reaction is stopped after a period of time under magnetic stirring and heating conditions. The product is dissolved in dichloromethane and purified by precipitation in ethanol to obtain a quaternary triblock intermediate product; (3) After the second step reaction is completed, the purified intermediate is dissolved in dichloromethane, and alkyl mercaptan and photosensitizer 2,2-dimethoxy-2-acetophenone are added, and the alkyl mercaptan reacts with the double bond under ultraviolet light radiation to obtain a grafted alkyl long-chain triblock copolymer product; The molar ratio of allyl glycidyl ether to the dual initiator catalyst is 3000:1-1000:1; the molar ratio of tetrachlorophthalic anhydride to epoxide 1 is 1:20-1:2; the molar ratio of tetrachlorophthalic anhydride to allyl glycidyl ether is 1000:2000-4000:2000; the amount of alkyl mercaptan added is 1-1.2 times the number of C=C double bonds contained in the triblock copolymer, and the amount of photosensitizer added is 0.05-0.5% of the mass of the triblock copolymer.
[0012] Preferably, the single initiation catalyst is a heterogeneous metal catalyst, a homogeneous metal catalyst or a Lewis acid and an organic amine or an organic ammonium salt two-component catalyst; the dual initiation catalyst is a Lewis acid and a diquaternary ammonium salt two-component catalyst.
[0013] Preferably, the heterogeneous metal catalyst is a zinc compound / multiple active hydrogen compound mixed system, a rare earth metal complex and a double metal cyanide; the homogeneous metal catalyst is a metal porphyrin complex, a metal porphyrin complex, a β-diimine zinc catalyst or a multi-nuclear metal complex with a macrocyclic ligand; the Lewis acid is an organic boron compound.
[0014] Preferably, the mono-initiator catalyst is triethylamine, tributylamine, bis(triphenylphosphorane)ammonium chloride, tetra-n-butylammonium bromide, tetra-n-butylammonium chloride, tetrabutylamine succinate, tetrabutylamine terephthalate or 1,8-diazabicyclo[5.4.0]undec-7-ene; the di-initiator is tetrabutylamine succinate, tetrabutylamine terephthalate or tetrabutylamine isophthalate.
[0015] Preferably, the reaction temperature is 50-70° C., the reaction pressure is 1-3 MPa, and the total reaction time is 20-50 hours.
[0016] Preferably, the wavelength of the ultraviolet light in step (3) is 375 nm and the light intensity is 35 mw / cm 2 , the illumination time is 1-20min, and the reaction temperature is room temperature.
[0017] In the polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer, the weight content of the polyester molecular chain segment is 20-80%, and the weight content of the polycarbonate molecular chain segment is 80-20%.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention obtains a polyester-polycarbonate-polyester copolymer having a triblock structure by catalytically initiating ternary copolymerization of epoxide 1, epoxide 2, carbon dioxide and highly active tetrachlorophthalic anhydride. Tetrachlorophthalic anhydride is a cheap, readily available raw material with very high reactivity. The polyester chain segment prepared by copolymerizing it with epoxide has very high strength and glass transition temperature. The present invention selects epoxide with flexible links to copolymerize with carbon dioxide to obtain a polycarbonate chain segment with very high toughness, and the chain segment has a very low glass transition temperature. The linear polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer prepared by the present invention has two glass transition temperatures (T g1 <-20℃, T g2 ≥100℃) and better resilience, and the mechanical properties are also better than traditional elastomers. The polycarbonate segments formed by long-chain epoxide 1 and carbon dioxide have a lower glass transition temperature (T g1 <-20℃); the polyester segments formed by tetrachlorophthalic anhydride and short-chain epoxides have a high glass transition temperature (T g2 ≥100℃), so the triblock copolymer has two obvious glass transition temperatures, and its unique microphase separation structure gives it the thermoplastic processability of plastics and the high elasticity of rubber.
[0019] (2) The polyester-CO2-based polycarbonate-polyester triblock biodegradable elastomer prepared by the present invention is non-toxic, not easy to migrate or leach. It is synthesized from carbon dioxide, meets the goals of carbon peak and carbon neutrality, is green and environmentally friendly; it is fully biodegradable and is an environmentally friendly material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The hydrogen nuclear magnetic spectra of the carbon dioxide-based polycarbonate and the polyester-carbon dioxide-based polycarbonate-polyester triblock copolymer obtained in reaction step 1 and step 2 of Example 3 of the present invention.
[0021] Figure 2 This is the H NMR spectrum of the triblock copolymers of carbon dioxide-based polycarbonate, polyester-carbon dioxide-based polycarbonate-polyester and polyester-thiol grafted carbon dioxide-based polycarbonate-polyester obtained in reaction steps 1, 2 and 3 of Example 8 of the present invention. DETAILED DESCRIPTION Example 1
[0022] In an anhydrous and oxygen-free environment, 6.7 g of hexyl oxide, 43 mg of tetrabutylammonium isophthalate and 800 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.0 MPa of carbon dioxide, and reacted at 60 ° C for 15 hours. After the reactor was cooled, a small amount of product was taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 4.8 g of tetrachlorophthalic anhydride and 16 g of propylene oxide were added to the reactor and the reaction was continued at 60 ° C for 6 hours. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and precipitated in ethanol to obtain a triblock polymer. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 54.3 kDa, PDI1 = 1.16; the conversion rate of oxirane is 97%, and the amount of cyclic carbonate generated is 5wt%; Second step reaction: Mn2 = 61.8 kDa, PDI2 = 1.21; polyester content 29.8wt%, polycarbonate content 70.2wt%; T g1 =-5℃, T g2 =100℃; tensile strength 19MPa, elongation at break 840%. Example 2
[0023] In an anhydrous and oxygen-free environment, 8.52g of octane oxide, 43mg of tetrabutylammonium isophthalate and 800μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.0 MPa of carbon dioxide, and reacted at 60°C for 25h. After the reactor was cooled, a small amount of product was taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 4.8g of tetrachlorophthalic anhydride and 16g of propylene oxide were added to the reactor and the reaction was continued at 60°C for 6h. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and precipitated in ethanol to obtain a triblock polymer. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 45.8 kDa, PDI1 = 1.31; the conversion rate of octane oxide is 98%, and the amount of cyclic carbonate generated is 6wt%; Second step reaction: Mn2 = 58.6 kDa, PDI2 = 1.36; polyester content 30.6wt%, polycarbonate content 69.4 wt%; T g1 =-5℃, T g2 =100℃; tensile strength 18MPa, elongation at break 880%. Example 3
[0024] In an anhydrous and oxygen-free environment, 12.4 g of octyl glycidyl ether, 43 mg of tetrabutylammonium isophthalate and 800 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.0 MPa of carbon dioxide, and reacted at 60 ° C for 30 hours. After the reactor was cooled, a small amount of product was taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 4.8 g of tetrachlorophthalic anhydride and 16 g of propylene oxide were added to the reactor and the reaction was continued at 60 ° C for 6 hours. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and the triblock polymer was precipitated in ethanol. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 54.9 kDa, PDI1 = 1.37; the conversion rate of octyl glycidyl ether is 95%, and the amount of cyclic carbonate generated is 6wt%; second step reaction: Mn2 = 64.9 kDa, PDI2 = 1.41; polyester content 29.6 wt%, polycarbonate content 70.4 wt%; T g1 =-31℃, T g2 =100℃; tensile strength 18MPa, elongation at break 900%. The H NMR spectrum of the tetrachlorophthalic anhydride / propylene oxide / octyl glycidyl ether / carbon dioxide tetrablock copolymer obtained is as follows: Figure 1 shown. Example 4
[0025] In an anhydrous and oxygen-free environment, 12.4 g of octyl glycidyl ether, 43 mg of tetrabutylammonium isophthalate and 800 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.0 MPa of carbon dioxide, and reacted at 60 ° C for 30 h. After the reactor was cooled, a small amount of product was taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 5.7 g of tetrachlorophthalic anhydride and 23 g of propylene oxide were added to the reactor and the reaction was continued at 60 ° C for 6 h. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and the triblock polymer was precipitated in ethanol. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 54.3 kDa, PDI1 = 1.38; the conversion rate of octyl glycidyl ether is 94%, and the amount of cyclic carbonate generated is 7wt%; Second step reaction: Mn2 = 69.9 kDa, PDI2 = 1.40; polyester content 38.1wt%, polycarbonate content 61.9wt%; T g1 =-30℃, T g2 =101℃; tensile strength 20MPa, elongation at break 860%. Example 5
[0026] In an anhydrous and oxygen-free environment, 12.4g of octyl glycidyl ether, 43mg of tetrabutylammonium isophthalate and 800μL of triethylboron solution were added to a 50mL high-pressure reactor in sequence, filled with 1.0MPa of carbon dioxide, and reacted at 70°C for 25h. After the reactor was cooled, a small amount of product was taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 4.8g of tetrachlorophthalic anhydride and 16g of propylene oxide were added to the reactor and the reaction was continued at 60°C for 6h. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and the triblock polymer was precipitated in ethanol. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 49.9 kDa, PDI1 = 1.39; the conversion rate of octyl glycidyl ether is 97%, and the amount of cyclic carbonate generated is 13%; Second step reaction: Mn2 = 63.7 kDa, PDI2 = 1.44; polyester content 30.1%, polycarbonate content 60.9%; T g1 =-31℃, T g2 =101℃; tensile strength 19 MPa, elongation at break 870%. Example 6
[0027] In an anhydrous and oxygen-free environment, 2.4g of tetrachlorophthalic anhydride, 8g of propylene oxide, 12.4g of octyl glycidyl ether, 50mg of bis(triphenylphosphine) ammonium chloride and 90μL of triethyl boron solution were added to a 50mL high-pressure reactor in sequence, filled with 1.0 MPa of carbon dioxide, and reacted at 60°C for 40h. After the reactor was cooled, a small amount of product was first taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 2.4g of tetrachlorophthalic anhydride and 8g of propylene oxide were added to the reactor and the reaction was continued at 60°C for 6h. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and the triblock polymer was precipitated in ethanol. After the polymer was vacuum dried, molecular weight testing, nuclear magnetic resonance, thermal properties and mechanical properties were analyzed. First step reaction: Mn1 = 38.5 kDa, PDI1 = 1.57; the conversion rate of octyl glycidyl ether is 97%, and the amount of cyclic carbonate generated is 18%; second step reaction: Mn2 = 44.8 kDa, PDI2 = 1.41; polyester content 35.3wt%, polycarbonate content 64.7%; T g1 =-31℃, T g2 =100℃; tensile strength 20MPa, elongation at break 600%. Example 7
[0028] In an anhydrous and oxygen-free environment, 11.4 g of allyl glycidyl ether, 32.2 mg of tetrabutylammonium isophthalate and 600 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.5 MPa of carbon dioxide, and reacted at 45 ° C for 36 hours. After the reactor was cooled, a small amount of the product was first taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 8.6 g of tetrachlorophthalic anhydride and 29 g of propylene oxide were added to the reactor and the reaction was continued at 50 ° C for 12 hours. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and precipitated in ethanol to obtain a quaternary triblock polymer intermediate. After the polymer was vacuum dried, a small amount was taken for molecular weight testing and nuclear magnetic resonance analysis. The purified quaternary triblock polymer intermediate was dissolved in dichloromethane, 1.8g of n-octyl mercaptan and 0.1g of 2,2-dimethoxy-2-acetophenone were added, n-octyl mercaptan reacted with double bonds under ultraviolet radiation, the reaction mixture was added dropwise to the stirred ethanol for precipitation, and then the dissolution and precipitation were repeated three times to obtain the grafted alkyl long-chain triblock copolymer. After vacuum drying, the polymer was tested for molecular weight, NMR, thermal properties and mechanical properties. The first step reaction: Mn1 = 61.5kDa, PDI1 = 1.17; AGE conversion rate was 75%, and the cyclic carbonate content was 7%; the second step reaction: Mn2 = 86.7kDa, PDI2 = 1.23; the third step reaction: Mn3 = 101.3 kDa, PDI3 = 1.21; polyester content 48.4wt%, polycarbonate content 34.9%, polyether content 16.7%; T g1 =-28℃, T g2 =101℃; tensile strength 16MPa, elongation at break 1310%. Example 8
[0029] In an anhydrous and oxygen-free environment, 11.4 g of allyl glycidyl ether, 32.2 mg of tetrabutylammonium isophthalate and 600 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.5 MPa of carbon dioxide, and reacted at 45 ° C for 36 hours. After the reactor was cooled, a small amount of the product was first taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 8.6 g of tetrachlorophthalic anhydride and 29 g of propylene oxide were added to the reactor and the reaction was continued at 50 ° C for 12 hours. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and precipitated in ethanol to obtain a quaternary triblock polymer intermediate. After the polymer was vacuum dried, a small amount was taken for molecular weight testing and nuclear magnetic resonance analysis. The purified quaternary triblock polymer intermediate was dissolved in dichloromethane, 2.3g of n-butyl mercaptan and 0.1g of 2,2-dimethoxy-2-phenylacetophenone were added, n-butyl mercaptan reacted with double bonds under ultraviolet radiation, the reaction mixture was added dropwise to stirred ethanol for precipitation, and then the dissolution and precipitation were repeated three times to obtain the grafted alkyl long-chain triblock copolymer. After vacuum drying, the polymer was tested for molecular weight, NMR, thermal properties and mechanical properties. The first step reaction: Mn1 = 60.8 kDa, PDI1 = 1.14; AGE conversion rate was 73%, and the cyclic carbonate content was 8%; the second step reaction: Mn2 = 84.9 kDa, PDI2 = 1.19; the third step reaction: Mn3 = 95.7 kDa, PDI3 = 1.24; polyester content 55.4 wt%, polycarbonate content 29.7%, polyether content 14.9%; T g1 =-23 ℃, T g2 =100 ℃; tensile strength 17MPa, elongation at break 1260%. The H NMR spectra of the obtained allyl glycidyl ether / carbon dioxide binary copolymer, tetrachlorophthalic anhydride / propylene oxide / allyl glycidyl ether / carbon dioxide quaternary block copolymer and grafted alkyl long chain block copolymer are as follows: Figure 2 shown. Example 9
[0030] In an anhydrous and oxygen-free environment, 11.4 g of allyl glycidyl ether, 32.2 mg of tetrabutylammonium isophthalate and 600 μL of triethylboron solution were added to a 50 mL high-pressure reactor in sequence, filled with 1.5 MPa of carbon dioxide, and reacted at 45 ° C for 36 h. After the reactor was cooled, a small amount of the product was first taken out in an anhydrous and oxygen-free environment for molecular weight testing and nuclear magnetic resonance analysis. Then 8.6 g of tetrachlorophthalic anhydride and 29 g of propylene oxide were added to the reactor and the reaction was continued at 50 ° C for 12 h. After the reaction was completed, the carbon dioxide pressure was released, the product was dissolved with dichloromethane, and precipitated in ethanol to obtain a quaternary triblock polymer intermediate. After the polymer was vacuum dried, a small amount was taken for molecular weight testing and nuclear magnetic resonance analysis. The purified quaternary triblock polymer intermediate was dissolved in dichloromethane, 1.3g of n-dodecyl mercaptan and 0.1g of 2,2-dimethoxy-2-acetophenone were added, n-dodecyl mercaptan reacted with double bonds under ultraviolet radiation, the reaction mixture was added dropwise to the stirred ethanol for precipitation, and then the dissolution and precipitation were repeated three times to obtain the grafted alkyl long-chain triblock copolymer. After vacuum drying, the polymer was tested for molecular weight, NMR, thermal properties and mechanical properties. The first step reaction: Mn1 = 62.2 kDa, PDI1 = 1.16; AGE conversion rate was 76%, and the cyclic carbonate content was 5%; the second step reaction: Mn2 = 85.3 kDa, PDI2 = 1.37; the third step reaction: Mn3 = 114.2kDa, PDI3 = 1.26; polyester content 39.4wt%, polycarbonate content 44.5wt%, polyether content 16.1%; T g1 =-38 ℃, T g2 =101 ℃; tensile strength 13MPa, elongation at break 1460%.
Claims
1. A polyester-carbon dioxide-based polycarbonate-polyester triblock biodegradable elastomer, characterized in that It is a tetrachlorophthalic anhydride / epoxide 1 / epoxide 2 / carbon dioxide quaternary triblock copolymer; The epoxide 2 is epoxyhexane, epoxyoctane, butyl glycidyl ether, octyl glycidyl ether or allyl glycidyl ether; When epoxide 2 is oxirane, octane oxide, butyl glycidyl ether or octyl glycidyl ether, tetrachlorophthalic anhydride and epoxide 1 are polymerized to form a hard polyester segment, and epoxide 2 reacts with carbon dioxide to form a soft polycarbonate segment, the structure of which is shown in the following formula (a); If the epoxide 2 is allyl glycidyl ether, a polycarbonate with a double bond at the end of the branch chain is generated. Under ultraviolet light conditions, the terminal double bond further undergoes a thiol-ene click reaction with thiol to obtain a grafted alkyl long chain, the structure of which is shown in the following formula (b): wherein a≥1, b≥1, and a and b are both integers; 。 2. The polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer according to claim 1, characterized in that The epoxide 1 is ethylene oxide, propylene oxide, epichlorohydrin or butylene oxide.
3. The polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer according to claim 1, characterized in that When epoxide 2 is allyl glycidyl ether, the tetrachlorophthalic anhydride / epoxide 1 / allyl glycidyl ether / carbon dioxide quaternary triblock copolymer further undergoes a thiol-alkenyl click reaction with n-butyl mercaptan, sec-butyl mercaptan, isobutyl mercaptan, n-pentyl mercaptan, 2-pentyl mercaptan, isopentyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan, n-octyl mercaptan, sec-octyl mercaptan, isooctyl mercaptan, n-decyl mercaptan, n-nonyl mercaptan, tert-nonyl mercaptan, dodecanethiol, tetradecanethiol, hexadecanethiol or n-octadecyl mercaptan to obtain a grafted alkyl long chain.
4. A method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer as claimed in claim 1, characterized in that The preparation method of tetrachlorophthalic anhydride / epoxide 1 / epoxide 2 / carbon dioxide quaternary triblock copolymer includes the following two methods: Method 1: (a) adding part of epoxide 1, epoxide 2, part of tetrachlorophthalic anhydride and a single initiator catalyst to a high-pressure reactor under anhydrous and oxygen-free conditions, introducing carbon dioxide, and reacting for a period of time under magnetic stirring and heating conditions before stopping; (b) after the reaction is completed, cooling the reactor; adding the remaining same amount of epoxide 1 and tetrachlorophthalic anhydride under anhydrous and oxygen-free conditions, continuing the reaction for a period of time, and then obtaining a purified quaternary triblock copolymer by precipitation and drying; the molar ratio of total epoxide 1 to epoxide 2 is 1:10~1:1; the molar ratio of epoxide 2 to total tetrachlorophthalic anhydride is 6:1~2:1; the molar ratio of epoxide 2 to single initiator catalyst is 2000:1~500:1; Method 2: (a) Add epoxide 2 and a dual initiator catalyst into a high-pressure reactor under anhydrous and oxygen-free conditions, introduce carbon dioxide, react for a period of time under magnetic stirring and heating conditions, and then stop; (b) After the reaction is completed, cool the reactor; add epoxide 1 and tetrachlorophthalic anhydride under anhydrous and oxygen-free conditions, continue to react for a period of time, and then obtain a purified quaternary triblock copolymer by precipitation and drying; the molar ratio of epoxide 1 to epoxide 2 is 1:10~1:1; the molar ratio of epoxide 2 to tetrachlorophthalic anhydride is 6:1~2:1; the molar ratio of epoxide 2 to the dual initiator catalyst is 3000:1~1000:
1.
5. A method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer as claimed in claim 4, characterized in that The preparation of polyester-carbon dioxide-based polycarbonate-polyester triblock copolymer by reaction of tetrachlorophthalic anhydride / epoxide 1 / allyl glycidyl ether / carbon dioxide / thiol comprises the following steps: (1) Adding a dual initiator catalyst and allyl glycidyl ether into a high-pressure reactor under anhydrous and oxygen-free conditions, injecting carbon dioxide, and reacting for a period of time under magnetic stirring and heating conditions and then stopping; (2) After the reaction is completed, the reactor is cooled to room temperature, and tetrachlorophthalic anhydride and epoxide 1 are added under anhydrous and oxygen-free conditions. The reaction is stopped after a period of time under magnetic stirring and heating conditions. The product is dissolved in dichloromethane and purified by precipitation in ethanol to obtain a quaternary triblock intermediate product; (3) After the second step reaction is completed, the purified intermediate is dissolved in dichloromethane, and alkyl mercaptan and photosensitizer 2,2-dimethoxy-2-acetophenone are added, and the alkyl mercaptan reacts with the double bond under ultraviolet light radiation to obtain a grafted alkyl long-chain triblock copolymer product; The molar ratio of allyl glycidyl ether to the dual initiator catalyst is 3000:1-1000:1; the molar ratio of tetrachlorophthalic anhydride to epoxide 1 is 1:20-1:2; the molar ratio of tetrachlorophthalic anhydride to allyl glycidyl ether is 1000:2000-4000:2000; the amount of alkyl mercaptan added is 1-1.2 times the number of C=C double bonds contained in the triblock copolymer, and the amount of photosensitizer added is 0.05-0.5% of the mass of the triblock copolymer.
6. The method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer according to claim 4 or 5, characterized in that The single initiation catalyst is a heterogeneous metal catalyst, a homogeneous metal catalyst or a Lewis acid and an organic amine or an organic ammonium salt two-component catalyst; the dual initiation catalyst is a Lewis acid and a diquaternary ammonium salt two-component catalyst.
7. The method for preparing a polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer according to claim 6, characterized in that The heterogeneous metal catalyst is a zinc compound / multiple active hydrogen compound mixed system, a rare earth metal complex and a double metal cyanide; the homogeneous metal catalyst is a metal porphyrin complex, a metal porphyrin complex, a β-diimine zinc catalyst or a multinuclear metal complex with a macrocyclic ligand; the Lewis acid is an organic boron compound.
8. The method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer according to claim 7, characterized in that The mono-initiator catalyst is triethylamine, tributylamine, bis(triphenylphosphorane)ammonium chloride, tetra-n-butylammonium bromide, tetra-n-butylammonium chloride, tetrabutylamine succinate, tetrabutylamine terephthalate or 1,8-diazabicyclo[5.4.0]undec-7-ene; the di-initiator is tetrabutylamine succinate, tetrabutylamine terephthalate or tetrabutylamine isophthalate.
9. The method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer as claimed in claim 4 or 5, characterized in that The reaction temperature is 50-70° C., the reaction pressure is 1-3 MPa, and the total reaction time is 20-50 hours.
10. The method for preparing the polyester-carbon dioxide based polycarbonate-polyester triblock biodegradable elastomer as claimed in claim 5, characterized in that The wavelength of the ultraviolet light in step (3) is 375nm and the light intensity is 35mw / cm 2 , the illumination time is 1-20min, and the reaction temperature is room temperature.
Citation Information
Patent Citations
Bio-based elastomer prepared from carbon dioxide and preparation method thereof
CN109485842A
Phthalic anhydride / tetrachlorophthalic anhydride / epoxide / carbon dioxide quadripolymer and preparation method thereof
CN118206728A
Tetrachlorophthalic anhydride / epoxide / carbon dioxide ternary block copolymer and preparation method thereof
CN118206729A
Tetrachlorophthalic anhydride / ethylene oxide / propylene oxide / carbon dioxide quadripolymer and preparation method thereof
CN118206730A
Cited By
Preparation method of block polyester-polycarbonate
CN120965980A
A process for the preparation of a block polyester-polycarbonate
CN120965980B